Functions of screen space in shots by Mieczysław Jahoda in the example of his first feature films: Zimowy zmierzch and Pętla - Maron, Marcin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2020)
The text is devoted to discussing the formation methods and the functions of screen space in shots by Mieczysław Jahoda in the films Zimowy zmierzch (directed by S. Lenartowicz) and Pętla (directed by W.J. Has). Mieczysław Jahoda is presented as one of the main initiators of stylistic changes in the films of Polish School in the mid 1950s. The analysis concerns the camera means applied by Jahoda in order to obtain screen effects: light, frame composition, photographic optics and perspective transformation. The film shots by Mieczysław Jahoda are characterized by an exceptional ability to evoke mental space, emotions, memory and imagination via the shapes of screen space. Their feature is a special esthetization aimed at creating the atmosphere of films, as well as symbolic and cultural references.